DISEMINASI SISTEM MULTIPLANTING PENANAMAN MANGROVE SEBAGAI UPAYA REHABILITASI HUTAN MANGROVE DI PESISIR TIMUR PULAU BANGKA - Bidayani, Endang; Reniati, Reniati; Priyambada, Agung (Jurnal Abdi Insani, 2024)
The eastern coastal communities of Bangka Island are vulnerable to ecological disasters. This is due to the destruction of mangrove forests in the area, one of which is the impact of tin mining activities. Mangroves play a role in mitigating the climate crisis. Therefore, efforts to rehabilitate damaged mangrove forests should be carried out massively. The problems currently faced by partners are: 1) Partners do not yet have the skills to rehabilitate mangrove multiplanting systems; and 2) Partners do not have knowledge regarding the multiplanting system. This activity aims to: 1) Help partners rehabilitate mangrove forests damaged by multiplanting systems with a high success rate; and 2) Restore the function of the mangrove forest ecosystem as a habitat for aquatic biota as a commodity caught by fishermen around the forest location. The outputs resulting from this activity are: 1) Increase in mangrove forest area using a multiplanting system; 2) Increasing community understanding and skills to conserve mangrove forests; and 3) Availability of mangrove nurseries. Implementation of PkM on the coast of Kekerjak Village and Batu Be Lubang Village. The activity method is participatory or involves the Kedetik and Batu Be Lubang Village Governments in the PkM stage which is focused on two activities, namely socialization and implementation of activities. As a result of the activities, the mangrove plants planted in the multiplanting system grew well. The planted plant seeds are protected with sacks filled with sand so they don't get washed away by the waves. Replacement is carried out for dead mangroves. Multiplanting system planting using more than one tree in one planting hole is expected to have better survival compared to one tree in one planting hole.